PENGETAHUAN HAK KEKAYAAN INTELEKTUAL (HKI) DOSEN DALAM UPAYA MENINGKATKAN KESADARAN BER-HKI CIVITAS ACADEMICA - Derta .; Endang Purwaningsih (Universitas Pamulang, 2016)
All members of academia—lecturers and students—who are the front liners in developing science and technology should be sufficiently equipped with the know-how on intellectual property rights (IPR), not only the ones related to patent rights but also those related to industrial design rights. This knowledge is crucial in helping all academia members to grow respect for copyrights. Since it is the academia members who produce intellectual work, the lecturers at YARSI University should be educated on the matter. And, as preliminary measures, research to map this issue at YARSI University is necessary. This research is applied normative/empirical normative/empirical juridical, that is, it stresses on the secondary data in analyzing the principles in positive laws and in analyzing factors which are related to the research object, and analyzing its implementation in promoting intellectual property rights among lecturers. The mapping findings of this research conducted at YARSI University with 50 full-time respondents suggest that: the majority (64%) comprehends the issue while 36% others don’t; most lecturers (66%) cannot differentiate copyright from patent right while the other 34% can; some (30%) of the respondents can categorize intellectual rights (trademark, design, PVT, trade secrets) while 70% others cannot; most lecturers (62%) are informed of plagiarism and its related laws while 38% others are not; 52% of the lecturers cannot differentiate such terms as creator, copyright, inventor, and invention while 48% others can; 96% of the respondents are not aware of automatic protection while 8% others are; 96% of the respondents are not informed of the object of copyright and its scope as described in the latest law (UU No.28 2014) while the other 4% are; 58% of the respondents are clueless on outright sale, royalty, and license while 42% others are not; 80% of the respondents know whether or not it is allowed to have a book copied for personal purposes while the other 20% don’t; it is a relief to learn that 86% of the respondents are aware of the importance of having an invention listed although 14% others are not; most lecturers (60%) cannot differentiate such terms as ‘listed’, ‘registered’, and ‘published’, while 40% others can; all respondents (100%) do not know anything about copyright-related offenses which can be filed to court. Some measures taken to promote awareness of intellectual property rights among lecturers at YARSI University are education on the issue and reward for it in the form of incentives for performing lecturers with scientific publications and registered patents. At YARSI University, it is Deputy Rector II ex-officio Research Head who has the authority and plays the role in motivating the lecturers to conduct research and to earn intellectual property rights.Keywords: lecturers’ knowledge on IPR, awareness of IPR, academia